2020
DOI: 10.1016/j.dark.2020.100565
|View full text |Cite
|
Sign up to set email alerts
|

Duel of cosmological screening lengths

Abstract: Two distinct perturbative approaches have been recently formulated within General Relativity, arguing for the screening of gravity in the ΛCDM Universe. In this paper we compare them and show that the offered screening concepts, each characterized by its own interaction range, can peacefully coexist. Accordingly, we advance a united scheme, determining the gravitational potential at all scales, including regions of nonlinear density contrasts, by means of a simple Helmholtz equation with the effective cosmolog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…It is worth noting that the selected values of eff serve well in depicting the observable Universe as they both satisfy eff < 1: for the chimney topology studied here, the lower bound on physical periods of the tori is of the order of 20 Gpc [1]. Additionally, according to [18], the current value of the effective screening length is approximately 2.6 Gpc, so the ratio eff /( ) , in terms of these values, limits the physically interesting range for eff today.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that the selected values of eff serve well in depicting the observable Universe as they both satisfy eff < 1: for the chimney topology studied here, the lower bound on physical periods of the tori is of the order of 20 Gpc [1]. Additionally, according to [18], the current value of the effective screening length is approximately 2.6 Gpc, so the ratio eff /( ) , in terms of these values, limits the physically interesting range for eff today.…”
Section: Resultsmentioning
confidence: 99%
“…As we have indicated earlier, Equations (1) and, therefore, (2) do not incorporate the effects of peculiar motion. In [18], however, it has been shown that the role of such contribution is essential in the cosmological setting and that peculiar velocities may be effectively reintroduced by using the effective cosmological screening length λ eff (see formula (41) of [18]) in replacement of the screening length λ in Equations (1) and (2). At this point, this amounts to substituting with eff in the right-hand side of (4) and (5), which yields…”
Section: Methodsmentioning
confidence: 99%
“…As we have noted previously, the peculiar motion of gravitating bodies is disregarded in Equation ( 1) and, consequently, in (4). Nevertheless, the significance of such a contribution has recently been pointed out in [29], where the authors have also shown that peculiar velocities may be effectively restored by employing the effective screening length λ eff (given by the Formula (41) of [29]) instead of the screening length λ in Equations ( 1) and ( 4). Specifically, in the matter-dominated epoch, the two quantities λ eff and λ are related to one another as λ eff = √ 3/5λ.…”
Section: Methods the Model And Basic Equationsmentioning
confidence: 99%
“…(2.4) with the corresponding solutions (2.16) and (2.23) does not take into account the peculiar velocities of gravitating masses. However, in [23], the authors argued the importance of such account. It was demonstrated that the peculiar velocities can be included back into consideration effectively in eq.…”
Section: Basic Equations and Alternative Solutionsmentioning
confidence: 99%